2007
DOI: 10.1111/j.1747-6593.2007.00079.x
|View full text |Cite
|
Sign up to set email alerts
|

Sewerage network modelling in Latvia, use of InfoWorks CS and Storm Water Management Model 5 in Liepaja city

Abstract: The existing partially combined sewerage system in the city of Liepaja, Latvia, is in a poor structural condition and hydraulic overloading causes flooding and pollution. As part of a wider project to upgrade water services in the city, supported by the European Union (EU) cohesion fund (CF), a mathematical model of the system was constructed and verified. In determining appropriate software for use, two key objectives had to be considered: (i) fast model construction to allow upgrading works to be designed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 1 publication
0
17
0
Order By: Relevance
“…Through numerical simulations, the effectiveness in different LID scenarios was evaluated in three aspects, which was the runoff volume reduction, the peak discharge reduction and the traffic congestion relief, respectively. The duration of ponding depth over 15 cm and its corresponding shortening percentage were selected as the variables for evaluating the effectiveness in relieving the traffic congestion and adding it to the related effectiveness analysis was different from the previous research [18,36,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through numerical simulations, the effectiveness in different LID scenarios was evaluated in three aspects, which was the runoff volume reduction, the peak discharge reduction and the traffic congestion relief, respectively. The duration of ponding depth over 15 cm and its corresponding shortening percentage were selected as the variables for evaluating the effectiveness in relieving the traffic congestion and adding it to the related effectiveness analysis was different from the previous research [18,36,38].…”
Section: Discussionmentioning
confidence: 99%
“…SWMM has been updated several times, and its functions have been improved significantly [37]. Compared with other models, SWMM has a better simulation effect [38], and it has been widely used in the evaluation and forecasting of the surface runoff process of storm floods by relevant scholars. Marsalek et al [33] conducted in-depth studies on 12 storm events in three typical small watersheds in the United States and found that the SWMM simulation results fit well with the measured runoff results.…”
Section: Hydrological Model Selectionmentioning
confidence: 99%
“…Urban flood modelling has long been the works of hydrological communities, and a few models have been proposed, such as the ILLUDAS model (Terstriep and Stall, 1974), SWMM model (Cole and Shutt, 1976), TR-55 (USDA, 1986), HSPF model (Bicknell et al, 1993), Inforworks model (Koudelak and West, 2008), STORM model (Wiles and Levine, 2002), etc. These models are proposed mainly for urban flood planning and management, which focus on the underground pipeline water transportation, and do not have the function to calculate the surface runoff which is the main cause of urban flooding.…”
Section: Urban Flood Forecasting Modellingmentioning
confidence: 99%
“…InfoWorks CS is a stormwater modelling tool, developed and introduced by Wallingford Software UK. It combines a relational database with geographical analysis to provide a single environment for network modelling [9]. Comparing to SWMM, InfoWorks CS provides a more stable fully dynamic engine [10].…”
Section: Modelling Of Stormpav Green Pavement System With Storm Watermentioning
confidence: 99%